Analisis Perencanaan Kebutuhan Sarana Dan Prasarana Pada Suku Dinas Kesehatan Jakarta Pusat - Nuraini Apriliana Putri; Christian Wiradendi Wolor; Marsofyati Marsofyati (Universitas 17 Agustus 1945 Semarang, 2023)
This study aims to determine how the process of planning facilities and infrastructure in the Suku Dinas Kesehatan Central Jakarta. This research uses qualitative research methods, namely by analyzing the problems and data found. Qualitative research is based on primary and secondary data. Primary data in this study was obtained by conducting observations, interviews, and documentation, while secondary data was obtained through journals, articles, and previous research related to the research topic. This research design is based on a qualitative approach and takes several samples. Respondents of this study are employees involved in facilities and infrastructure at the research site. Planning of facilities and infrastructure is carried out so that all office facilities and infrastructure can run well, so that employees in the office can utilize them optimally, can also support employee performance and smooth work so that maximum final results can be obtained. The purpose of this study was to determine how the planning of facilities and infrastructure in the Suku Dinas Kesehatan Central Jakarta.